Desenvolvimento e aplicação de um sistema de gerenciamento de manutenção “no code” em bubble - Santos Júnior, Ricardo Oliveira dos (2023)
The collection and standardization of maintenance records within a company are essential, as they will be the basis for decision-making by the management team. To optimize this process, large companies often employ integrated or outsourced systems to carry out this crucial task. However, not all companies can afford the licensing costs associated with these mentioned software solutions, so alternative options must be considered. With the growth of technology and automation, low-code development tools that require minimal or no coding are becoming increasingly popular due to their practicality and efficiency compared to traditional development methods.Therefore, this work will introduce a “no-code” development technology called “Bubble”, and an application will be developed for the collection, standardization, and organization of these maintenance records, which will later be used to create indicators to assist in the company's maintenance planning. The system was implemented in a textile industry within the spinning sector, specifically for a type of machine called “Open End” used for spinning elements. Finally, the system yielded positive outcomes concerning cost reduction and potential for delivering indicator results.